Effect of modified carbon black on the properties of natural rubber vulcanizate - Ghosh A K; Adhikari B; Maiti S; Mustafi S K; Ray G S (Journal of Applied Polymer Science, 1997)
Rubber-grade carbon black filler HAF (N330) was modified with a plant product (PP; long aliphatic chain substituted phenols), proprietary item under patent application, in the presence or absence of hexamine (Hexa) or dicumyl peroxide (DCP) to put a flexible moiety in between the carbon black and the elastomer chain in order to improve some of its processing and reinforcement characteristics in natural rubber (NR). The modification process is simple and involves cheap materials. The modified carbon black was characterized and evaluated for its processability as well as reinforcing characteristics in NR vulcanizate. It was observed to show better processing behavior, without any processing aid, such as easy incorporation and uniform dispersion in the rubber phase without abnormal heat generation, and also improved vulcanizate properties, such as tensile strength, flex cracking resistance, and lower abrasion loss, without affecting other properties to a significant extent.
Keywords: Abrasion loss; Bound rubber; Carbon black modification; Flex cracking; Heat buildup